Adolescent Substance Use Following a Deadly U.S. Tornado Outbreak: A Population-Based Study of 2, 000 Families. Issue 5 (3rd September 2017) - Danielson, Carla Kmett; Sumner, Jennifer A.; Adams, Zachary W.; McCauley, Jenna L.; Carpenter, Matthew; Amstadter, Ananda B.; Ruggiero, Kenneth J.
Abstract : Despite conceptual links between disaster exposure and substance use, few studies have examined prevalence and risk factors for adolescent substance use and abuse in large, population-based samples affected by a recent natural disaster. We addressed this gap using a novel address-based sampling methodology to interview adolescents and parents who were affected by the 4th deadliest tornado outbreak in U.S. history. Postdisaster interviews were conducted with 2, 000 adolescent–parent dyads living within a 5-mile radius of the spring 2011 U.S. tornadoes. In addition to descriptive analyses to estimate prevalence, hierarchical linear and logistic regression analyses were used to examine a range of protective and risk factors for substance use and abuse. Approximately 3% reported substance abuse since the tornado. Greater number of prior traumatic events and older age emerged as consistent risk factors across tobacco and alcohol use and substance abuse since the tornado. Tornado incident characteristics, namely, greater loss of services and resources after the tornado and posttraumatic stress disorder since the tornado, were associated with greater alcohol consumption. Service loss increased risk for binge drinking, whereas, for substance abuse, posttraumatic stress disorder increased risk and parent presence during the tornado decreased risk. Greater family tornado exposure was associated with a greater number of cigarettes smoked in female but not male teen participants. Both trauma and non-trauma-related factors are relevant to postdisaster substance abuse among adolescents. Future research should examine the role of broader ecological systems in heightening or curtailing substance use risk for adolescents following disaster exposure.